2020
DOI: 10.3390/jcm9010158
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Effects of MCM7 Variants, Somatic Mutations, and Clinical Features on Acute Myeloid Leukemia Susceptibility and Prognosis

Abstract: The main objective of the study was to evaluate the associations between MCM7 rs2070215, rs1527423, and rs1534309 single nucleotide polymorphisms (SNPs) and acute myeloid leukemia (AML) risk and prognosis. The secondary objectives were to assess if any relationships existed between the mentioned SNPs and FLT3, DNMT3A, NPM1 mutations with clinical outcomes and overall survival (OS) in AML patients. We investigated 281 AML cases and 405 healthy subjects. The results showed a significant association between a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Clinical characteristics such as treatment (low dose treatment), patients' outcome, high LDH level, high PLT count, high WBC count, high cytogenetic and ELN risk, high age (>60 years) at diagnosis, and FLT3 ITD mutation were associated with lower OS (p < 0.01), as expected. Part of the mentioned OS associations have been previously reported in the literature [2,41,52,53] and our group also reported part of these clinical associations on smaller cohorts of AML patients [31,32,53].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Clinical characteristics such as treatment (low dose treatment), patients' outcome, high LDH level, high PLT count, high WBC count, high cytogenetic and ELN risk, high age (>60 years) at diagnosis, and FLT3 ITD mutation were associated with lower OS (p < 0.01), as expected. Part of the mentioned OS associations have been previously reported in the literature [2,41,52,53] and our group also reported part of these clinical associations on smaller cohorts of AML patients [31,32,53].…”
Section: Discussionsupporting
confidence: 77%
“…We included only subjects who signed the written informed consent form, with complete laboratory and clinical records, in which the genotyping investigation was successfully performed. AML diagnosis was based on clinical examination and laboratory investigation (including complete blood count, blood smear, bone marrow and/or blood microscopic examination, flow cytometry, cytogenetics, fusion gene investigation as reported previously [30], DNA copy number variations analysis as reported previously [31], fragment analysis for FLT3-ITD and NPM1 mutations as reported previously [32][33][34], and target next-generation sequencing as reported previously [34]).…”
Section: Patients and Controlsmentioning
confidence: 99%
“…Interestingly, the statistical results in our study were robust, both nonadjusted and adjusted models; these results are similar to previous studies that LDH is a prognostic factor for AML. 4,16 In particular, the effect was more obvious in those with LDH ≥570 U/L, and such a result may remind the clinicians of devoting more attention and more care to these AML patients.…”
Section: Discussionmentioning
confidence: 96%
“…Former studies show high concentration of LDH, and age is associated with a high risk for early mortality in AML patients. 10 , 15 , 16 Increased LDH levels are the product of the enhanced glycolytic activity of the tumor and tumor necrosis due to hypoxia, the latter being related to a high tumor burden. 10 Most previous studies have indicated that serum LDH is an independent prognostic factor for patients with AML (non‐APL); 3 , 4 , 17 the higher the serum LDH level, the shorter the survival time.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA (gDNA) was extracted from peripheral blood specimens collected in 2 mL EDTA vacutainer tubes by using PureLink Genomic DNA Mini Kits (Thermo Fisher Scientific, Waltham, MA, USA) and Wizard Genomic DNA Purification kits (Promega, Madison, WI, USA) with minor modification [ 25 ]. The concentration and purity of the obtained DNA samples were measured by a BioSpectrometer basic (Eppendorf, Wien, Austria).…”
Section: Methodsmentioning
confidence: 99%